2014
DOI: 10.1039/c4np00008k
|View full text |Cite
|
Sign up to set email alerts
|

Biologically active diterpenes containing a gem-dimethylcyclopropane subunit: an intriguing source of PKC modulators

Abstract: Covering: 1973 to 2013. The biological activities of tigliane, lathyrane, ingenane, casbane, jatropholane and premyrsinane diterpenoids which contain the gem-dimethylcyclopropyl unit are described. Particular attention is given to their anti-viral, anti-microbial and cytotoxic activities. In the main text there are 132 references. The electronic supplementary information contains tables listing 424 of these diterpenoids, their occurrence and biological activity together with the references.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 119 publications
1
54
0
1
Order By: Relevance
“…All the isolates we reported here contain this moiety or the subunit derived from it. This information suggests that they may share the similar biosynthetic intermediate and machinery, which is consistent with the literatures' report [34][35][36] that the lathyrane is the common precursor of the other skeletons we isolated. First, the 8,14-and 6,12-cyclization of lathyrane led to tigliane and premyrsinane, respectively.…”
Section: Accepted Manuscriptsupporting
confidence: 92%
See 2 more Smart Citations
“…All the isolates we reported here contain this moiety or the subunit derived from it. This information suggests that they may share the similar biosynthetic intermediate and machinery, which is consistent with the literatures' report [34][35][36] that the lathyrane is the common precursor of the other skeletons we isolated. First, the 8,14-and 6,12-cyclization of lathyrane led to tigliane and premyrsinane, respectively.…”
Section: Accepted Manuscriptsupporting
confidence: 92%
“…Its molecular formula was indicated as C 34 H 52 O 14 from the HR-ESI-MS data (m/z 707.3238 [M + Na] + , calcd for 707.3255). Examination of its NMR data with those of 5 suggested that 6 was the product of acetylation at HO-15 in 5.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…The casbane skeleton ( 1 ), along with cembranes ( 3 ) and lathyranes ( 4 ), which originate from geranylgeranyl diphosphate ( 5 ), are biosynthetically positioned directly en route to the extensively reported tigliane system ( 2 ), represented by well‐known phorbol esters (Scheme ) . Casbanes also display considerable biological activity, mostly towards various cancer cell lines, which is comparable with many biologically active diterpenes containing a gem ‐dimethylcyclopropane unit …”
Section: Introductionmentioning
confidence: 98%
“…Although sesquiterpenes [1][2][3][4][5][6] and diterpenes [7][8][9][10][11] have been the subject of numerous reviews, sesquiterpenes containing a gemdimethylcyclopropyl subunit need a comprehensive review because of the wide range of their potentially valuable biological activities and broad structural diversity.…”
Section: Introductionmentioning
confidence: 99%